Effect of unilateral and bilateral resistance exercise on maximal voluntary strength, total volume of load lifted, and perceptual and metabolic responses - Costa, Eduardo C; Moreira, Alexandre; Cavalcanti, Bruno; Krinski, Kleverton; Aoki, Marcelo S (Biology of Sport, 2015)
The present study investigated the effect of unilateral and bilateral resistance exercise (RE) on maximal voluntary strength, total volume of load lifted (TVLL), rating of perceived exertion (RPE) and blood lactate concentration of resistance-trained males. Twelve healthy men were assessed for the leg extension one-repetition maximum (1RM) strength using bilateral and unilateral contractions. Following this assessment, an RE session (3 sets of repetitions to failure) was conducted with bilateral and unilateral (both limbs) contractions using a load of 50% 1RM. The TVLL was calculated by the product of the number of repetitions and the load lifted per repetition. RPE and blood lactate were measured before, during and after each set. Session RPE was measured 30 minutes after RE sessions. There was a significant difference in the bilateral (120.0±11.9) and unilateral (135.0±20.2 kg) 1RM strength (p<0.05). The TVLL was similar between both RE sessions. Although the repetitions decreased with each successive set, the total number of repetitions completed in the bilateral protocol (48) was superior to the unilateral (40) protocol (p<0.05). In both bouts, RPE increased with each subsequent set whilst blood lactate increased after set 1 and thereafter remained stable (p<0.05). The RPE and lactate responses were not significantly different between both sessions. In conclusion, a bilateral deficit in leg extension strength was confirmed, but the TVLL was similar between both RE sessions when exercising to voluntary fatigue. This outcome could be attributed to the number of repetitions completed in the unilateral RE bout. The equal TVLL would also explain the similar perceptual and metabolic responses across each RE session.